2016
DOI: 10.1038/ni.3581
|View full text |Cite|
|
Sign up to set email alerts
|

USP15 regulates type I interferon response and is required for pathogenesis of neuroinflammation

Abstract: Genes and pathways in which inactivation dampens tissue inflammation present new opportunities for understanding the pathogenesis of common human inflammatory diseases, including inflammatory bowel disease, rheumatoid arthritis and multiple sclerosis. We identified a mutation in the gene encoding the deubiquitination enzyme USP15 (Usp15) that protected mice against both experimental cerebral malaria (ECM) induced by Plasmodium berghei and experimental autoimmune encephalomyelitis (EAE). Combining immunophenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 64 publications
3
85
2
Order By: Relevance
“…Futhermore, late blockade of IFNAR1 in partially ECM‐susceptible IRF7‐deficient mice, provided evidence that type I IFN‐signalling also acted late, perhaps on brain‐recruited CD8 + T cells, as originally suggested by Ball et al . In a more recent study, activation of type I IFN responses in neurological tissue via the deubiquitinase enzyme USP15 and the E3 Ubiquitin ligase TRIM25 promoted ECM, further supporting the concept that type I IFN‐signalling in the brain may be deleterious during P. berghei ANKA infection . Therefore, although type I IFN‐signalling clearly induces ECM symptoms in this model, the precise mechanisms by which this occurs remain to be fully determined.…”
Section: Effect Of Type I Ifn‐signalling During Experimental Cerebralsupporting
confidence: 63%
“…Futhermore, late blockade of IFNAR1 in partially ECM‐susceptible IRF7‐deficient mice, provided evidence that type I IFN‐signalling also acted late, perhaps on brain‐recruited CD8 + T cells, as originally suggested by Ball et al . In a more recent study, activation of type I IFN responses in neurological tissue via the deubiquitinase enzyme USP15 and the E3 Ubiquitin ligase TRIM25 promoted ECM, further supporting the concept that type I IFN‐signalling in the brain may be deleterious during P. berghei ANKA infection . Therefore, although type I IFN‐signalling clearly induces ECM symptoms in this model, the precise mechanisms by which this occurs remain to be fully determined.…”
Section: Effect Of Type I Ifn‐signalling During Experimental Cerebralsupporting
confidence: 63%
“…Since SOCS1 inhibits type I IFN‐induced signaling and type I IFN signaling in astrocytes regulates neuroinflammation in EAE (Rothhammer et al , ; Torre et al , ), we studied the impact of OTUB1 on IFN‐β‐induced astrocyte activation. Upon IFN‐β stimulation, phosphorylation of STAT1 was induced in both OTUB1‐competent and OTUB1‐deficient astrocytes with a stronger induction in OTUB1‐deficient cells (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data show that STAT1 activation and chemokine mRNA production of astrocytes induced by IFN‐β can also be partially suppressed by OTUB1. Interestingly, Torre et al () showed that a loss‐of‐function mutation in USP15 ameliorates EAE by dampening type I interferon signaling, which drives the production of chemokines and cytokines in the spinal cord. Therefore, OTUB1 might ameliorate EAE by inhibiting both type I and type II interferon responses in astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…USP15 in involved in multiple cellular processes, including p53 (Liu et al, 2017;Zou et al, 2014) and NF-kB (Schweitzer et al, 2007) signaling, histone H2B deubiquitination (Long et al, 2014), and the transforming growth factor-β (TGF-β) pathway (Eichhorn et al, 2012;Inui et al, 2011;Iyengar et al, 2015), and showed interaction with a number of ubiquitin linkages in vitro . Interestingly, recent studies have linked USP15 to inflammation in experimental models, through the regulation of type I and type II interferon (IFN) responses (Pauli et al, 2014;Torre et al, 2017;Zou et al, 2014;Zou et al, 2015). Also, by diminishing TGF-β signaling, depletion of USP15 was shown to reduce the proliferation and the oncogenic capacity of patient-derived glioma-initiating cells (Eichhorn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%